Metaphorical Argumentation - Romero, Esther; Soria, Belén (Informal Logic)

(untitled) (Informal Logic, 2021)
It is a fact that novel metaphorical utterances appear in natural language argumentation. It seems, moreover, that these put forward metaphorical propositions that can have different roles (data, warrants or claims) in argument structure. There can even be good argumentation which is indispensably metaphorical. However, not all metaphor theories provide an explanation of metaphorical meaning compatible with these claims. In this article, we explain the three main views on metaphorical meaning and show, analysing some examples, their consequences for metaphorical argumentation. Our analysis shows that only the cognitive view can explain that there are arguments which can only be generated using novel metaphors.